2020
DOI: 10.1111/ffe.13215
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure, mechanical, and fatigue behaviours of MAG welded G20Mn5 cast steel

Abstract: The microstructure, mechanical strength, and fatigue response of metal active gas (MAG) butt‐welded G20Mn5 cast steel was thoroughly investigated for exploring the service safety and reliability of new‐generation railway bogie frames. The fatigue properties of the matrix and welded joints were determined by both low‐ and high‐cycle service regimes. On the basis of nanoindentation testing, the fatigue crack growth (FCG) was derived by correlating with cyclic plastic response of microdomain materials across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…From Figure 11 , it has been observed that the dendritic microstructures are formed having long columnar grains at the interface ( Figure 11 b) and cellular dendrites ( Figure 11 c). The fusion zone microstructure at this section revels formation of secondary dendritic arm, the magnifying image shows the formation of intermetallic phase whose presence is confirmed through the EDS report ( Figure 11 d), the grains are parallel and distributed uniformly with mix coarse and fine columnar dendritic (uniaxial) which might be due to the proper mixing of material at the fusion zone [ 38 , 39 ]. Figure 12 shows the SEM images of the weld cross section, i.e., at the interface and the fusion zone; this shows the microstructure with no directional solidification with columnar and cellular dendritic structure.…”
Section: Resultsmentioning
confidence: 72%
“…From Figure 11 , it has been observed that the dendritic microstructures are formed having long columnar grains at the interface ( Figure 11 b) and cellular dendrites ( Figure 11 c). The fusion zone microstructure at this section revels formation of secondary dendritic arm, the magnifying image shows the formation of intermetallic phase whose presence is confirmed through the EDS report ( Figure 11 d), the grains are parallel and distributed uniformly with mix coarse and fine columnar dendritic (uniaxial) which might be due to the proper mixing of material at the fusion zone [ 38 , 39 ]. Figure 12 shows the SEM images of the weld cross section, i.e., at the interface and the fusion zone; this shows the microstructure with no directional solidification with columnar and cellular dendritic structure.…”
Section: Resultsmentioning
confidence: 72%
“…The global behavior is very close to the one determined by Han [ 20 ] for G20Mn5QT cast steel at R = −1 (green dashed line). However, a significant difference with the curve from Wu’s study [ 21 ] who characterized the material at R = 0.1 (dotted green line). This difference hints at a significant influence of the average stress on the fatigue life.…”
Section: Low Cycle Fatigue Testsmentioning
confidence: 59%
“…To the best of our knowledge, no detailed analyses of the influence of micro-shrinkages without the presence of macro porosities on low cycle fatigue damage of cast steels are available. Nevertheless, Han [ 20 ] highlighted that cracks initiate around those porosities in G20Mn5QT grade during high cycle fatigue (HCF) tests; as well as Wu in a G20Mn5N grade during low cycle fatigue (LCF) tests [ 21 ]. Moreover, Nagel studied the impact of internal and surface porosities inside cast specimens in G20Mn5Q grade during HCF tests [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [24] in their work. The second approach rests on using just one sample at higher levels of stress.…”
Section: Diameter Ofmentioning
confidence: 93%
“…The first approach requires more samples to be tested at lower stress amplitudes (levels). This approach makes it possible to determine a confidence interval for the resulting S-N curve, and was chosen, e.g., by Wu et al [24] in their work. The second approach rests on using just one sample at higher levels of stress.…”
Section: Diameter Ofmentioning
confidence: 99%